Financing the Development of Waqf Property: The Experience of Malaysian and Singapore - Mustafa Mohd Hanefah; Abdullaah Jalil; Asharaf Mohd Ramli; Hisham Sabri; Norhaziah Nawai; Syahidawati Hj. Shahwan (Universiti Sains Islam Malaysia, 2024)
This paper studies financing mechanisms used by waqf institutions in Malaysia and Singapore in developing various type of waqf properties. In Malaysia, the duty of managing and developing waqf assets is under the jurisdiction of state government through State Islamic Religious Councils (SIRCs). The problem of getting enough funds and inefficient staffs has hindered the development of a large number of waqf assets especially land waqf. In addition to traditional mode of financing such as long lease (hukr), modern scheme and self-financing have been used by the authority to develop waqf properties. Interestingly, the development of waqf assets in Singapore is encouraging especially after the establishment of Warees Pte. Ltd.: a subsidiary of Singapore Islamic Religious Council (MUIS). The source of financing is mainly generated through cash waqf contributed monthly by Muslims in Singapore. Besides that, modern a modern mode of financing such as sukuk musyarakah has been introduced in developing commercial buildings in waqf land. This paper compares the financing methods adopted to develop waqf properties in Malaysia and Singapore. Recommendations are made as to the best form of financing that can be adopted in developing waqf properties in Malaysia.